Brucella suis in armadillos (Chaetophractus villosus) from La Pampa, Argentina - Kin, Marta Susana; Fort, Marcelo Cristian; Torioni, Susana Marta; Casanave, Emma Beatriz (Elsevier, 2018)
Brucellosis is a zoonotic disease transmitted from an animal reservoir to humans. Both, wildlife and domestic animals, contribute to the spreading of these zoonosis. The surveillance of the animal health status is strictly regulated for domestic animals, whereas disease monitoring in wildlife does not exist. The aim of the present study was to provide data on the prevalence of anti-Brucella antibodies in Chaetophractus villosus from a region of La Pampa, Argentina to assess public health risks. The C. villosus is endemic to South America, and in Argentina it represents a food resource for human consumption. A total of 150 sera of armadillos bleeding between 2007 and 2010 were tested using buffered plate antigen test (BPAT), serum agglutination test (SAT), 2-mercaptoethanol (2-ME) and complement fixation test (CFT), for the detection of anti-Brucella antibodies. Antibodies to Brucella sp. were found in 16% (24:150) of the armadillos tested using the BPAT test. All 24 positive samples were confirmed by the SAT, 2-ME and CFT tests. Strain isolation was attempted from liver and spleen samples of two animals with positive serology. Isolates were characterized by conventional biotyping and identification of specific DNA using polymerase chain reaction (PCR). A total of 2 isolates were recovered from spleen and liver. Both of them were identified as Brucella suis biovar 1. This preliminary study provides the first report on the seroprevalence of brucellosis and describes the first isolate of B. suis biovar 1 in C. villosus in Argentina.